Strengthening digital Islamic activism: virtual ethnography of Bandung Hijrah Youth’s WhatsApp engagement - Abdurrahman, Muhammad Sufyan; Salma, Aqida Nuril; Parsono, Slamet; Ali, Aditya; Widyaningrum, Septiana Yustika (Faculty of Communications Science, Dr. Soetomo University, 2025)
The Hijrah Movement in Greater Bandung represents a dynamic form of digitally mediated Islamic activism, where WhatsApp Groups (WAGs) play pivotal roles in dawah engagement. However, research on how digital platforms shape religious identity, trust formation, and communal accountability in online Islamic communities remains limited. This study examined how the hyper-personal model can explain the role of WAGs in fostering relational intimacy and sustaining collective identity within a movement. Using a qualitative virtual ethnography approach, including in-depth interviews and content analysis of WAG Kopdar Masjid BDG Raya, this research investigates the mechanisms through which asynchronous communication, selective self-presentation, and feedback loops influence community engagement. Findings reveal that WAGs enhance perceived trust and belonging by enabling curated self-disclosure, reinforcing positive group norms, and facilitating collaborative decision-making. These digital interactions strengthen spiritual bonds and extend to offline initiatives such as charity programs and Dawah safaris, bridging digital and traditional religious mobilisation. The study advances the hyper-personal model by demonstrating its applicability to digitally mediated Islamic activism. It offers empirical evidence that digital platforms reshape authority structures, spiritual discourse, and social cohesion in contemporary Islamic communities. It also highlighted the potential risks of misinformation, echo chambers, and platform dependency. This research mainly contributes to Islamic studies, digital communication, and social movements, providing insights into the complex interplay between online and offline religious engagement.